Краткая эколого-фаунистическая характеристика листоедов-скрытоглавов (Chrysomelidae, Cryptocephalinae) лесной зоны Украины - Огуль, Р.А. (Вестник зоологии, 1973)
52 species of leaf beetles from the subfamily Cryptocephalinae are listed for the forest zone of the Ukrainian SSR, 16 species of them are mentioned for the first time. Mesophylic forms, and forest and meadow mesophylls in particular, prevail in the Cryptocephalinae fauna of the forest zone. The steppe mesophylls are not numerous and con¬fined to the steppizated meadows and steppe areas. Chrysomelidae feed on leaves and generative organs of 68 plant species. Most species of Cryptocephalinae are associated with woody shrubby plants. Five zoogeographical groups are distinguished in the Cryptocephalinae fauna.